Banks as Catalysts for Industrialization - Da Rin, Marco; Hellmann, Thomas (Journal of Financial Intermediation, 2002)
We provide a new theory of the role of banks as catalysts for industrialization. In their influential analysis of continental European industrialization, Gerschenkron and Schumpeter argued that banks promoted the creation of new industries. We formalize this role of banks by introducing financial intermediaries into a “big push” model. We show that banks may act as catalysts for industrialization provided they are sufficiently large to mobilize a critical mass of firms and that they possess sufficient market power to make profits from coordination. The theory provides simple conditions that help explain why banks seem to play a creative role in some but not in other emerging markets. The model also shows that universal banking helps to reduce the cost of acting as catalyst. Journal of Economic Literature Classification Numbers: G21, N2, O14, O16.